Online Game-Based Learning for Hand Hygiene Practices Among Young Children in Indonesia: A Quasi-Experimental Study - Yuri Nurdiantami; Hilda Agil; Tokie Anme (CV FOUNDAE, 2026)
Hand hygiene remains a cornerstone of infection prevention due to its crucial role in reducing the transmission of infectious diseases across community and healthcare settings. However, establishing consistent handwashing habits among young children remains challenging despite school-based health education programs. Game-based learning has emerged as a promising approach to enhance engagement and support behavior change in early childhood education, yet empirical evidence from developing countries remains limited. This study aims to evaluate the effectiveness of an online game-based educational intervention in improving hand hygiene performance among early childhood children in Indonesia. A quasi-experimental pretest–posttest design was conducted with 50 parent–child pairs involving children aged 4–6 years in Bekasi City. Participants accessed an online educational game designed to teach proper handwashing practices over one week. Baseline and follow-up observations were conducted to assess behavioral change. As the data were not normally distributed (Shapiro–Wilk W = .97, p = .03), the Wilcoxon signed-rank test was applied. Results showed a significant improvement in hand hygiene scores from pretest (Mdn = 3.0) to posttest (Mdn = 15.0), Z = −6.034, p < .001, with a large effect size (r = .60). These findings support the use of digital games as an effective and innovative learning tool to promote health-related behaviors among young children.